ANALISIS KONTEN DAN KOMPARATIF GOOD CORPORATE GOVERNANCE REPORT & CORPORATE SOCIAL RESPONSIBILITY REPORT BERDASARKAN PEDOMAN UMUM GCG DAN STANDAR GRI G4 (Studi kasus pada Laporan Tahunan dan Sustainability Report Indo Tambangraya Megah dan Tambang Batubar - Rantetoding, Gloria Patricia; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is conducted to provide information about the implementation of Good Corporate Governance and Corporate Social Responsibility applied in each of report based on GCG Regulation (KNKG 2006) and GRI G4. This research is a qualitative research with case study approach on content of annual report and sustainability report from both of mining corporations, Indo Tambangraya Megah dan Tambang Batubara Bukit Asam year 2013. The results of this research shows that both of corporations has implemented good enough Good Corporate Governance even it can’t be seen directly to the company. For Corporate Social Responsibility, it well said based on report that both corporations completed 50% of all performance indicator in GRI G4.Corporations still have to make it more complete to achieve all of the performance indicator in the next report. And also their Good Corporate Governance towards a better future company. Keywords : Good Corporate Governance, Corporate Social Responsibility, mining, transparency, accountability, responsibility, independency, fairness.